Role of Magnetic resonance imaging in Evaluation of Orbital Mass Lesions - Bhawna Rohilla; 2.Mallika Vyas; Lavanya Dharmalingam, (Global Journal of Medicine and Public Health)
Background The prevalence of orbital pathologies is currently on the rise, likely due to heightened awareness of clinical symptoms, improved access to healthcare facilities, and the introduction of advanced diagnostic and treatment options. Most masses have an effect on the sensory and motor visual pathways. Early identification and the implementation of treatment are necessary to mitigate patient suffering caused by visual complications or the risk of permanent vision loss. Aim The aim and objectives of this study were to evaluate the role of MRI in diagnose, characterize & define the extent of various orbital mass lesions, with a focus on distinguishing between benign and malignant orbital lesions. Methodology In this cross sectional study, conducted over the duration of two years from December 2022 to November 2024 included 30 patients who came to department of radiodiagnosis, Aarupadai Veedu Medical College, Puducherry under Vinayaka Mission’s Research FoundationUniversity, Salem with clinical suspicious of orbital mass lesions. All these patients were subjected to MRI of the orbit with brain sections for further characterization of the mass lesion. Results In our study, out of 30 cases, extraconal were more prevalent 16 (53.33%). The most common benign orbital tumors were hemangiomas 5 (16.67%),followed by meningiomas 4 (13.33%), and inflammatory pseudotumors 3 (10%). The most common malignant orbital tumors were lymphomas 5 (16.67%), and metastasis 4 (13.33%). Conclusion Magnetic Resonance Imaging (MRI), along with its advanced techniques, has become a crucial imaging tool for assessing orbital lesions due to its exceptional soft tissue and contrast resolution, absence of ionizing radiation, capability for multi-planar imaging, and enhanced lesion characterization. Recent technological innovations such as Diffusion Weighted Imaging, Dynamic Contrast-Enhanced MRI significantly contribute to the diagnosis of various orbital masses.